IMPLEMENTASI PENDIDIKAN KARAKTER DI MADRASAH ALIYAH SUNAN PANDANARAN NGAGLIK SLEMAN YOGYAKARTA (Sebuah Kajian Dari Perspektif Pendidikan Islam dan Psikologi) - Sri Haningsih; Puji Rahayu (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Character education is getting the most attention from formal schools in Indonesia after the government announced that it is important to build the younger generation’s character. The character development is very important because many crimes are committed by high school students such as fighting, drug abuse, and motor-gang fights. This study aims to describe the implementation of character education in Madrasah Aliyah Sunan Pandanaran, which is a boarding school under Pondok Pesantren Pandanaran, and design character-education patterns suitable for MASPA. Descriptive qualitative research design was implemented by interviewing teachers and management staff at MASPA and observing the implementation of character education in MASPA. The results showed that 1) MASPA has been implementing character education in the 9 main character values namely religious character, honesty, tolerance, discipline, hard work, self-reliance, self-confidence, responsibility, and patriotism. 2) the implementation of character education is integrated with the regulations at Pondok Pesantren Sunan Pandanaran. Each character is developed with different activities. Some of the activities that are required leads in sanctions if it is not carried out by learners or students. 3) The suitable character education model for students of Madrasah Aliyah Sunan Pandanaran is by example. Nonetheless, implementation guide should be recorded so that it can still be implemented under different management. A design of good character education is also presented for MASPA.